A phenomenological investigation of Spanish-English bilingual supervisees’ experience in clinical supervision - Perry, Vanessa M (East Carolina University, 2016)
With a growing number of American households speaking languages other than English, the counseling profession must meet the counseling needs of non-English speaking clients. In turn, clinical supervisors and counselor educators must meet the needs of bilingual counselors. This existential phenomenological study examines the clinical supervision experience of Spanish-English bilingual supervisees. Participants' responses highlighted the compatibility or incompatibility of supervisor-supervisee knowledge and skills, the resilience and resourcefulness of Spanish-English bilingual supervisees, and the diversity of the Latino population. Overall, participants expressed the overwhelming desire to have a clinical supervisor that possessed cultural competence. The majority of participants also expressed interest in having a Spanish-English bilingual supervisor, although this proficiency was considered a luxury. Further research is needed to better understand the needs of Spanish-English bilingual supervisees.
Keywords: Clinical supervision; Bilingual supervision; Multicultural counseling; Practice Management; Multilingualism; Cultural Competency; Hispanic Americans; Humans; Language